Factors affecting financial restatements: evidence from public listed companies in Malaysia / Shafinaz Lyana Abu Talib - Abu Talib, Shafinaz Lyana (2015)
Perceptibly, various factors have an influence over the occurrence of financial restatements among companies. Based on prior studies, it is important to study the factors that are associated with the likelihood of financial restatements because the announcement of financial restatement will result in a lack of public trust towards large companies. Thus, this paper has two main objectives. The first objective is to examine whether firms that restate their financial statements have difference in levels and size in terms of client fees, provision of non-audit services (NAS), size of audit committee and types of auditors than non-restatement firms. The second objective is to test whether factors such as client fees, provision of non-audit services (NAS), size of audit committee and types of auditors will influence the occurrence of financial restatements among public listed companies in Malaysia. A sample consisting of 224 Malaysian public listed companies during the period of 2005 to 2014 is studied. A control group comprising of non-restating firms is formed using match-pair procedures where restated and non-restated firms are matched by size (total assets), industry, exchange board classification, and financial year-end. This study has found that the restatement firms are, on average, pay slightly lower level of client fees and NAS fees and have small size of audit committee compared to non-restatement companies. In addition, this study found that non-restatement companies compared to restatement companies are hiring Big 4 audit firms. The logistic regression is applied to test the hypothesis. This study found that types of auditors have a significant association with the incidence of financial restatements. Based on the result, the types of auditors have a negative relationship with the occurrence of financial restatements. This means that companies that hired Big 4 audit firms could reduce the possibility of restatements. In contrast, the other three variables are not found to be associated with future restatements. The main contributions of this paper are as follows: 1) this study was developed in order to extend previous research by using the sample from year 2005 up until 2014; 2) this study could act as the reference for the regulators and policymakers (Bursa Malaysia and Securities Commission) in policy deliberation or policy review and for the improvement of existing regulations and guidelines; and 3) the findings of this study might help the companies to reduce future restatements.